The Tasmanian Conception to Community (C2C) Study Database 2008-09 to 2013-14: Using linked health administrative data to address each piece in the puzzle. (September 2021) - Neil, Amanda L.; Chappell, Kate; Wagg, Fiona; Miller, April; Judd, Fiona
Abstract: Background: Tasmania, Australia has a small widely dispersed regional and rural population. The Conception to Community (C2C) Study Database was established as a research platform to inform service planning and policy development and improve health outcomes for Tasmanian mothers and children. The aims of this study were to establish by maternal socio-demographic characteristics: 1) the distribution of births in Tasmania; 2) hospital utilisation for children from birth to 5-years; and 3) the association between child and maternal emergency department (ED) presentation rates. Methods: Perinatal and public hospital ED and admitted patient data were linked for every child born in Tasmania between 2008-09 to 2013-14, and their mothers. Individualised rates of ED presentations and hospital admissions were calculated from birth to 5-years. Frequent presenters to ED were defined as having at least four presentations per annum. Ratios of ED presentation and hospital admission rates by sociodemographic characteristics (region (north, north-west, south), rurality, maternal age, and area socioeconomic disadvantage) were estimated using mixed-effects negative binomial models, with random intercepts for each child and family. Results: The C2C Database is comprised of records for 37, 041 children and 27, 532 mothers. One-in-ten Tasmanian babies lived in a remote area. The mean yearly rate of ED presentations per child varied by sex, age, region and rurality. Frequent presenters were more likely to reside in the north-west or north, in urban areas, have mothers under 20- years, be male, and live in more disadvantaged areas, with 2.3% of children frequent presenters in their first year of life. The odds of a child being a frequent presenter during their first-year was 6.1- times higher if the mother was a frequent presenter during this period. Conclusion: Associations between maternal and child health service use and combined effects of regionality and rurality highlight opportunities for targeted intervention and service innovations. Highlights: Mother and child linkage analysis examining health service use in early childhood. Strong associations identified between mothers and infants ED use. Socioeconomic and regional differences identified for ED and admitted patient use. A gradient of ED use found with rurality, with highest use among urban dwellers. Regional linkage yields evidence of service and policy-relevance at multiple levels.